Former Yugoslav Republic of Macedonia : Staff Report for the 2000 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The macroeconomic developments in the Former Yugoslav Republic of Macedonia were positive, despite the Kosovo crisis. Executive Directors welcomed this development, stressed the need to implement prudent financial policies, and accelerate structural reforms. They emphasized the need to improve corporate governance and enterprise performance through implementation of laws on bankruptcy procedures and creditors' rights. Directors noted the need for improvements in the reliability, coverage, and timeliness of economic data, and recommended the authorities to participate in the General Data Dissemination System.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet